Development of a piezoelectric energy harvesting system by mechanical vibrations aiming to apply in agricultural systems - Santos, Luciano Mendes dos (2022)
The advancement of technology in any area is due to need and time, so there will always be coexistence with this paradigm of technology evolution, a concept related to energy generation is associated with mechanical vibrations, known as Energy Harvesting, using piezoelectric devices (PZT). These devices installed in equipment, which eventually work in a vibration regime, such as machines and vehicles, can generate small amounts of energy from piezoelectricity, which refers to the property that some materials have to generate electric current when subjected to mechanical deformations. The objective of this work was to evaluate and characterize the use of piezoelectric materials in energy harvesting through mechanical vibrations from mass-spring systems associated with PZTs pellets. Initially, the characterization of an energy harvesting system composed of only one PZT tablet associated with a mass-spring system was carried out. For this purpose, two modes of treatment of the signal generated in the system were evaluated: a full wave rectifier with capacitor and a load manager module for commercial use. (LTC3588). The mass-spring system was conditioned to operate in resonance, whose natural frequency was 16.2 Hz, considering 5 repetitions. The voltage, current and electrical power generated by the system were determined, considering the different proposed rectification modes. In this context, an average power of 2.53mW was observed for the diode bridge and 1.50mW for the LTC3588 module. The rectification system influences the power generation process, and its design and adequacy to the system are of fundamental importance. The full-wave rectification system proved to be more efficient in the energy generation process when compared to the LTC3588 module, regardless of the evaluated response variable. Subsequently, an energy harvesting system was developed consisting of the association of 25 PZTs in parallel, series, and mixed (5S5P - 5 sets of PZTs in series and these sets connected in parallel to each other and 5P5S - 5 sets of PZTs in parallel and these sets connected in series with each other). The resonant frequency of the system was 16.2Hz, with frequency ranges above and below the natural frequency of the system being evaluated, considering 5 repetitions in each scenario. It was found that the 5P5S association was the one that showed the best result about the power generated at the natural frequency of the system, with an average power peak of 700mW. The system excitation frequency significantly influenced the energy generation process, in which the best excitation frequencies were obtained for a system operating under resonance conditions. The configuration composed of signal rectification by diode bridge together with the mixed association of PZT chips (with 5 sets of 5 PZTs in parallel and these sets connected in series with each other), proved to be promising for the development of energy harvesting by mechanical vibrations to be used in agricultural machinery and equipment.